Fine lava fiber as well as preparation method and application thereof
The integrated fiber forming and microwave curing process for lava fine fibers addresses the inefficiencies of basalt fiber production, achieving high production capacity and reduced costs with enhanced mechanical properties and temperature resistance.
Patent Information
- Application Number
- CN202411302202.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-20
AI Technical Summary
Basalt fiber production faces challenges with unstable drawing operations, high production costs, and low efficiency due to the difficulty in melting basalt ore, which has poor thermal permeability and a high crystallization temperature, leading to inconsistent material performance.
A method involving integrated fiber forming by spraying, spinning, and blowing, using a mixture of lava and functional ores, including iron ore, zircon, silica, and bauxite, with a mass ratio greater than 8:2, and microwave curing to produce lava fine fibers with a diameter of 3 to 6 μm, enhancing mechanical strength and temperature resistance.
The method significantly increases production efficiency and reduces costs by over 70%, achieves a production capacity 10 times that of basalt fiber, and improves mechanical properties and temperature resistance, while maintaining excellent wave transmission performance.
Smart Images

Figure CN119161095A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional fibers, and in particular relates to lava fine fibers and a preparation method and application thereof. Background Art
[0002] Basalt fiber, also known as basalt continuous fiber, is a type of lava fiber. The fiber diameter is usually 6 to 25 μm. It has the properties of high strength, acid, alkali and salt resistance, high and low temperature resistance, insulation and magnetic insulation, and good wave transmission. It is a low-cost substitute for carbon fiber and is used in aerospace military industry, safety chemical industry, industrial manufacturing, civil transportation, marine engineering, and automobile lightweighting. Basalt fiber is an inorganic mineral long fiber made of basalt formed by cooling volcanic magma as raw material, which is melted and clarified at high temperature and quickly drawn through an alloy bushing (platinum-rhodium alloy bushing, 400 to 800 holes). However, since basalt fiber uses pure basalt ore as raw material, the characteristics of the basalt raw material itself determine that basalt is difficult to melt, the melt has poor thermal permeability, and the crystallization temperature is high, which leads to unstable basalt fiber drawing operation and material performance, low production efficiency, and high production cost. Summary of the invention
[0003] The purpose of the present invention is to provide a lava fine fiber and a preparation method and application thereof. The preparation method provided by the present invention has high production efficiency and low production cost.
[0004] In order to achieve the above object, the present invention provides the following technical solutions:
[0005] The present invention provides a method for preparing lava fine fibers, comprising the following steps:
[0006] The melt is subjected to integrated fiber forming by spraying, spinning and blowing to obtain a fiber semi-finished product;
[0007] The semi-finished fiber product and the surface treatment agent are mixed and then solidified to obtain lava fine fibers;
[0008] The mass ratio of the lava ore to the functional ore is greater than 8:2; the functional ore includes iron ore, zircon, silica and bauxite;
[0009] The integrated fiber forming by spraying, spinning and blowing includes simultaneously performing fiber forming by spraying and fiber forming by spinning.
[0010] Preferably, the chemical composition of the lava ore includes, by mass percentage, 44-47% silicon oxide, 15-18% aluminum oxide, 17-20% calcium oxide, 7-10% magnesium oxide, 5-8% iron oxide and 1-2% titanium oxide.
[0011] Preferably, the functional ore comprises, by weight: 0.5 to 3 parts of iron ore, 2 to 3 parts of zircon, 4 to 6 parts of silica and 8 to 12 parts of bauxite;
[0012] The iron ore includes one or more of aluminum ore, iron ore and zirconium ore.
[0013] Preferably, the surface treatment agent includes a film-forming agent and a silane coupling agent;
[0014] The film former includes one or more of epoxy resin, polyester resin, polyurethane resin and vinyl resin.
[0015] Preferably, the mass ratio of the semi-finished fiber product to the surface treatment agent is 100:0.2-2.
[0016] Preferably, the melting temperature is 800-1500° C. and the melting time is 6-8 hours.
[0017] Preferably, the wind speed of the blowing fiber forming is 80-120 m / s, and the blowing pressure is 25-35 kPa; the rotation speed of the spinning fiber forming is 5000-7500 rpm, and the line speed is 90-140 m / s.
[0018] Preferably, the curing comprises microwave curing; the curing temperature is 180-250° C., and the curing time is 0.2-0.3 h.
[0019] The present invention provides lava fine fibers prepared by the preparation method described in the above technical solution, wherein the average diameter of the lava fine fibers is 3 to 6 μm, the tensile strength is 2600 to 4200 MPa, and the elastic modulus is 85 to 110 GPa.
[0020] The present invention provides the use of the lava fine fibers described in the above technical solution in reinforced composite materials, fire-resistant heat-insulating materials or filter materials.
[0021] The present invention provides a method for preparing lava fine fibers, comprising the following steps: mixing lava ore and functional ore, melting them to obtain a melt; spraying, spinning and blowing the melt to obtain a fiber semi-finished product; mixing the fiber semi-finished product with a surface treatment agent and solidifying it to obtain lava fine fibers; the mass ratio of the lava ore and the functional ore is greater than 8:2; the functional ore includes iron ore, zircon, silica and bauxite; the spraying, spinning and blowing integrated fiberization includes simultaneously performing spraying, spinning and blowing fiberization. The traditional basalt fiber drawing leak plate is mainly composed of 400 to 800 holes, and the production is still in the stage of single furnace and small pool kiln, with low production efficiency, which leads to high production cost. The present invention adopts a spraying, spinning and blowing integrated fiberization method (simultaneously performing spraying, spinning and spinning fiberization), which is essentially different from the leak plate drawing process. The spraying, spinning and blowing integrated fiberization method adopted by the present invention has a high degree of automation in the production of lava fine fibers, which can greatly reduce production costs. For factories of the same size, the production capacity of lava microfiber is more than 10 times that of basalt fiber; the energy consumption per ton of finished fiber of lava microfiber is about 30% of that of basalt fiber; the raw material cost per ton of finished fiber of lava microfiber is about 35% of that of basalt fiber (with the same equipment investment of 30 million, the annual production capacity of lava microfiber is about 40,000 tons, while the annual production capacity of basalt fiber is only about 3,000 tons; the energy consumption per ton of basalt fiber products is about 5,500 kWh, while the energy consumption per ton of lava microfiber is about 1,600 kWh; the direct cost per ton of basalt fiber products is about 10,000 yuan, while the direct cost per ton of lava microfiber is about 3,000 yuan), so the production cost is greatly reduced; in addition, the present invention adopts an integrated fiber making method of spraying, spinning and blowing, and the obtained lava microfiber has a low diameter and excellent mechanical properties and high temperature resistance. Basalt melt is usually accompanied by crystallization, and the crystallization temperature is close to the molding temperature of the fiber. The present invention adopts functional minerals to keep the melting temperature, melt viscosity and uniformity of the melt temperature relatively stable, and there are no crystallization nuclei in the fiber, thereby improving the quality of lava fine fiber production and structural stability, and improving the mechanical strength and temperature resistance of the lava fine fiber.
[0022] Furthermore, the present invention uses lava ores and functional ores from different regions and categories, and mixes them according to the chemical composition requirements and lithology gene combinations. Compared with basalt fiber using a single basalt ore as a fiber-making raw material, the present invention mixes the ingredients according to the use requirements, broadens the categories and application range of raw materials and fiber products, and improves the performance of lava fine fibers. In addition, the lava fine fibers of the present invention use microwave-cured lava fine fibers, and the obtained lava fine fibers have excellent wave transmission performance. Compared with the traditional thermal drying process, it reduces the energy loss in the production process, improves the production efficiency, and further reduces the production cost; the present invention also controls the wind speed and blowing pressure of the blowing fiber, and the rotation speed and line speed of the spinning fiber, so that the average fiber diameter of the lava fine fibers is 3 to 6 μm, which is significantly reduced compared to the fiber diameter of ordinary basalt fibers (>10 μm). BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Flow chart of the preparation of lava microfibers. DETAILED DESCRIPTION
[0024] The present invention provides a method for preparing lava fine fibers, comprising the following steps:
[0025] The lava ore and the functional ore are mixed and melted to obtain a melt;
[0026] The melt is subjected to integrated fiber forming by spraying, spinning and blowing to obtain a fiber semi-finished product;
[0027] The semi-finished fiber product and the surface treatment agent are mixed and then solidified to obtain lava fine fibers;
[0028] The mass ratio of the lava ore to the functional ore is greater than 8:2; the functional ore includes iron ore, zircon, silica and bauxite;
[0029] The integrated fiber forming by spraying, spinning and blowing includes simultaneously performing fiber forming by spraying and fiber forming by spinning.
[0030] In the present invention, unless otherwise specified, the reagents used are commercially available products well known to those skilled in the art.
[0031] The present invention mixes lava ore and functional ore, melts them, and obtains a melt. In the present invention, the mass ratio of the lava ore to the functional ore is greater than 8:2, preferably 8.5 to 10:2, more preferably 9 to 9.5:2, and most preferably 9.2 to 9.3:2; the lava ore preferably includes igneous rock; and the functional ore includes iron ore, zircon, silica, and bauxite.
[0032] In the present invention, the chemical composition of the lava ore preferably includes, by mass percentage, 44-47% silicon oxide, 15-18% aluminum oxide, 17-20% calcium oxide, 7-10% magnesium oxide, 5-8% iron oxide and 1-2% titanium oxide.
[0033] In terms of mass percentage, the chemical composition of the lava ore used in the present invention preferably includes 44-47% silicon oxide, more preferably 45-46%, and most preferably 45-45.5%.
[0034] Calculated by the mass percentage of the silicon oxide, the chemical composition of the lava ore used in the present invention preferably includes 15-18% aluminum oxide, more preferably 16-17%, and most preferably 16-16.5%.
[0035] Calculated by the mass percentage of the silicon oxide, the chemical composition of the lava ore used in the present invention preferably includes 17-20% calcium oxide, more preferably 18-19%, and most preferably 18-18.5%.
[0036] Calculated by the mass percentage of the silicon oxide, the chemical composition of the lava ore used in the present invention preferably includes 7-10% magnesium oxide, more preferably 8-9%, and most preferably 8-8.5%.
[0037] Calculated by the mass percentage of the silicon oxide, the chemical composition of the lava ore used in the present invention preferably includes 5-8% iron oxide, more preferably 6-7%, and most preferably 6-6.5%.
[0038] Calculated by the mass percentage of the silicon oxide, the chemical composition of the lava ore used in the present invention preferably includes 1-2% titanium oxide, more preferably 1.2-1.8%, and most preferably 1.4-1.6%.
[0039] In the present invention, the functional ore preferably includes, by weight, 0.5 to 3 parts of iron ore, 2 to 3 parts of zircon, 4 to 6 parts of silica and 8 to 12 parts of bauxite.
[0040] In terms of weight percentage, the functional ore used in the present invention preferably includes 0.5 to 3 parts of iron ore, more preferably 1 to 2.5 parts, and most preferably 1.5 to 2 parts.
[0041] Calculated by weight of the iron ore, the functional ore used in the present invention preferably includes 2 to 3 parts of zircon, more preferably 2.2 to 2.8 parts, and most preferably 2.4 to 2.6 parts.
[0042] Calculated by weight of the iron ore, the functional ore used in the present invention preferably includes 4 to 6 parts of silica, more preferably 4.5 to 5.5 parts, and most preferably 4.8 to 5 parts.
[0043] Calculated by weight of the iron ore, the functional ore used in the present invention preferably includes 8 to 12 parts of bauxite, more preferably 9 to 11 parts, and most preferably 10 to 10.5 parts.
[0044] In the present invention, the melting temperature is preferably 800-1500°C, more preferably 900-1200°C, and most preferably 1000-1100°C; the melting time is preferably 6-8h, more preferably 7-8h, and most preferably 7-7.5h. In the present invention, the melting preferably includes pre-melting and final melting in sequence; the pre-melting temperature is preferably 800-1000°C, more preferably 850-950°C, and most preferably 900-930°C; the pre-melting time is preferably 3-4h, more preferably 3.2-3.8h, and most preferably 3.4-3.6h; the final melting temperature is preferably 1400-1500°C, more preferably 1420-1480°C, and most preferably 1440-1460°C; the final melting time is preferably 3-4h, more preferably 3.2-3.8h, and most preferably 3.4-3.6h.
[0045] In the present invention, the melting preferably also produces flue gas, which is discharged into a waste gas treatment system for treatment and then discharged in a qualified manner.
[0046] The melt is subjected to integrated fiber forming by spraying, spinning and blowing to obtain a fiber semi-finished product.
[0047] In the present invention, the integrated fiber forming by spraying, spinning and blowing includes simultaneously performing the fiber forming by spraying and fiber forming by spinning. In the present invention, the wind speed of the fiber forming by spraying is preferably 80-120 m / s, more preferably 90-110 m / s, and most preferably 100-105 m / s; the blowing pressure of the fiber forming by spraying is preferably 25-35 kPa; the airflow used for the fiber forming by spraying is preferably air; the air is preferably blown by positive pressure, and more preferably by positive pressure blowing of a Roots blower; the rotation speed of the fiber forming by spinning is preferably 5000-7500 rpm, more preferably 6000-7000 rpm, and most preferably 6500-6800 rpm; the linear speed of the fiber forming by spinning is preferably 90-140 m / s, more preferably 100-130 m / s, and most preferably 110-120 m / s.
[0048] After obtaining the semi-finished fiber product, the present invention mixes the semi-finished fiber product with a surface treatment agent and solidifies the mixture to obtain lava fine fibers.
[0049] In the present invention, the surface treatment agent preferably includes a film-forming agent and a silane coupling agent; the film-forming agent preferably includes one or more of epoxy resin, polyester resin, polyurethane resin and vinyl resin; the silane coupling agent preferably includes one or more of silane coupling agent KH550, silane coupling agent KH560 and silane coupling agent KH570; the mass ratio of the fiber semi-finished product and the surface treatment agent is preferably 100:0.2-2, more preferably 100:0.5-1.5, most preferably 100:1-1.2; the mass ratio of the film-forming agent and the silane coupling agent is preferably 1:0.02-0.04, more preferably 1:0.02-0.03; the surface treatment agent is preferably used in the form of a surface treatment agent aqueous solution; the mass concentration of the surface treatment agent aqueous solution is preferably 8-10%, more preferably 8.5-9.5%, most preferably 9-9.2%. In the present invention, the surface treatment agent is preferably mixed with the fiber semi-finished product by compressed air atomization spraying; the pressure of the compressed air is preferably <0.5MPa, more preferably 0.15-0.4MPa, most preferably 0.2-0.3MPa.
[0050] Before the curing, the present invention preferably further comprises gathering the mixed fibers containing the surface treatment agent; the gathering preferably comprises negative pressure gathering; the pressure of the negative pressure gathering is preferably -3 to -2 kPa, more preferably -2.8 to -2.2 kPa, and most preferably -2.6 to -2.4 kPa.
[0051] In the present invention, the curing temperature is preferably 180-250°C, more preferably 200-240°C, and most preferably 220-230°C; the curing time is preferably 0.2-0.3h, more preferably 0.22-0.28h, and most preferably 0.24-0.26h; the curing preferably includes microwave curing; the power of the microwave curing is preferably 250-300kW, more preferably 260-290kW, and most preferably 270-280kW.
[0052] In the present invention, the microwave curing is preferably carried out in a vacuum microwave system; the vacuum microwave system preferably includes a hot air furnace, a circulating fan and a dehumidification fan. The present invention uses a hot air furnace thermocouple to heat the air and then blow it into the curing furnace to cure the surface treatment agent on the fiber surface. The dehumidification fan removes the humid hot air in the curing furnace, and the humid hot air passes through the curing furnace filter chamber and the spray system before being discharged in compliance with the standards. The vacuum microwave system is used to achieve zero emission, and the pure electric heating method (the hot air furnace uses a thermocouple to heat the air) basically achieves zero emission of tail gas.
[0053] The present invention adopts microwave curing, which has the following advantages compared with the conventional electrical heating drying method: the prepared lava fine fiber has good wave permeability, the microwave penetration heating process of the fiber from the inside to the outside is uniform, the temperature difference between the inside and the outside is small, and the situation of inconsistent heating temperature inside and outside in the conventional electrical heating method will not occur, and the fiber drying efficiency and fiber quality uniformity are high. The conventional electrical heating method requires a long time, slow speed, and high energy consumption. The use of microwave curing can directly heat the inside of the fiber, with a fast heating speed, high efficiency, and a greatly shortened drying cycle. At the same time, microwave curing does not require a heat transfer medium, has low energy consumption, and high curing efficiency. The microwave drying device has a small volume and occupies a small space, is easy to install and realize automatic continuous production, and at the same time, due to the characteristics of microwave power that can be quickly adjusted and has no inertia, the system equipment is easy to control, and the temperature can be adjusted arbitrarily between 40 and 250 ° C, which is easy to install and operate. Since microwave energy is controlled to work in a metal drying chamber and waveguide, there is very little microwave leakage, no radiation hazard and harmful gas emissions, no waste heat and dust pollution, neither pollutes the product nor the environment, and has high safety.
[0054] After the solidification is completed, the present invention preferably further comprises cooling, slitting and dust-filtering the solidified fibers obtained by the solidification. The present invention does not specifically limit the cooling and dust-filtering methods, and conventional cooling and dust-filtering methods in the art may be used. In the present invention, the slitting preferably comprises rotary slitting. The present invention adopts the rotary slitting method to prepare flocculent chopped fibers and filamentary chopped fibers at the same time, which greatly improves the production efficiency compared with the method of producing chopped fibers by secondary slitting of long fibers of basalt fibers and glass fibers.
[0055] The present invention provides lava fine fibers obtained by the preparation method described in the above technical solution, wherein the average diameter of the lava fine fibers is 3 to 6 μm; the tensile strength of the lava fine fibers is 2600 to 4200 MPa, preferably 2800 to 4000 MPa, more preferably 3000 to 3800 MPa, and most preferably 3500 to 3600 MPa; the elastic modulus of the lava fine fibers is 85 to 110 GPa, preferably 90 to 105 GPa, more preferably 95 to 100 GPa, and most preferably 96 to 98 GPa. The average diameter of the lava fine fibers obtained by the present invention is only 3 to 6 μm, the average diameter is small, and the mechanical properties and high temperature resistance are excellent.
[0056] The present invention provides the use of the lava fine fibers described in the above technical solution in reinforcing materials, synthetic materials, fire-resistant and heat-insulating materials or filter materials. In the present invention, the reinforcing material preferably includes cement concrete reinforcing materials or asphalt concrete reinforcing materials; the synthetic material preferably includes resin synthetic materials or plastic synthetic materials. In the present invention, the use temperature of the filter material is preferably 350-400°C, more preferably 360-390°C, and most preferably 370-380°C. The lava fine fibers provided by the present invention have a small average diameter, excellent mechanical properties and high temperature resistance, and have broad application prospects in reinforced composite materials, fire-resistant and heat-insulating materials or filter materials.
[0057] In order to further illustrate the present invention, a lava fine fiber provided by the present invention and its preparation method and application are described in detail below in combination with the accompanying drawings and embodiments, but they should not be understood as limiting the scope of protection of the present invention.
[0058] Example 1
[0059] Calculated by mass, the raw materials used in the preparation include 82 parts of lava ore (whose chemical composition, calculated by mass percentage, includes 46.56% silicon oxide, 16.24% aluminum oxide, 17.58% calcium oxide, 7.26% magnesium oxide, 7.88% iron oxide and 1.65% titanium oxide), 3 parts of iron ore, 2 parts of zircon, 5 parts of silica and 8 parts of bauxite.
[0060] Figure 1 The preparation flow chart of lava fine fibers is as follows:
[0061] Raw material system: Mix the prepared raw materials. Each production line uses 4 to 6 silos, two materials and one scale. The materials are fed by a long corridor conveyor or a lifting bucket, and the materials are fed by a mobile conveyor. There is also a screening device. The prepared raw materials are sent to their respective silos by a loading vehicle. Various raw materials are sent to the automatic metering and weighing system through the vibrating feeder at the bottom of the silo, and then the raw materials are transported by the conveyor. The whole process is automatically controlled by a computer. After the raw materials are mixed, they are transported to the melting system.
[0062] Melting system: The electric melting furnace is mainly divided into two sections: the preheating furnace and the melting furnace. The sections are connected by a secondary dispersed feeding system. The preheating furnace is mainly used for drying, preheating, heating and temperature increase of raw materials. The preheating furnace is controlled by PLC to realize automatic intermittent feeding and intermittent discharging according to time and flow control. The feeding temperature is room temperature, and the pre-melted discharging temperature is 925-950℃ for 3.5h. The secondary dispersed feeding system is mainly used for secondary distribution of raw materials to make the materials evenly distributed in the melting furnace. The melting furnace is equipped with 6 feeding ports, which are automatically dispersed and fed through gate valves and PLC control. The melting furnace is used to heat, melt and raise the temperature of preheated raw materials. The melting furnace is fed intermittently through the secondary dispersed feeding system, and the raw materials are melted and heated through electrical control. While feeding, the liquid material level in the melting furnace rises, and the liquid material is automatically discharged intermittently through the overflow port. The feeding temperature is 970-990°C, and the final melted discharge temperature is 1460-1480°C for 4 hours. The melt then passes through the homogenization and temperature control system of the overflow channel to ensure that the melt enters the centrifuge fiber forming machine through the chute at a stable flow rate at 1440-1460°C. The flue gas generated by the melting furnace is discharged into the waste gas treatment system for qualified discharge.
[0063] Fiber forming system: The melt flows out from the overflow port of the melting furnace and falls into the centrifuge through the movable flow slot. The centrifuge consists of a high-speed centrifugal roller and an air ring surrounding the centrifugal roller. When passing through the leak plate, the melt is blown into fibers and spun into fibers under the centrifugal force of the centrifugal roller with a speed of 7000rpm and the high-speed airflow with a pressure of 30kPa ejected by the high-pressure fan through the air ring. Nozzles are set around the centrifugal roller head and a spray hole is set in the center. Compressed air with a pressure of 0.45Mpa is used for atomization. Center and multi-point spraying are adopted. 1.2 parts of surface treatment agent (including 97 parts of film-forming agent and 3 parts of silane coupling agent KH550) are sprayed in the form of a jet, and the slag balls produced in the fiber-forming process are separated at the same time. The obtained fibers are blown into the fiber-collecting machine and adsorbed on the fiber-collecting mesh plate of the fiber-collecting machine by the negative pressure wind with a pressure of -3kPa to form a thin initial layer of fibers. The initial layer of fibers is sent to the pendulum machine through the transition conveyor. Under the reciprocating action of the pendulum belt, a multi-layer folded fine fiber structure is evenly formed on the forming conveyor arranged vertically therewith. Two centrifuges are set up in the fiber-forming system at the same time, one of which is a spare one, and the centrifuge rollers are cooled by forced water. The flue gas generated in the fiber-forming process is discharged after purification.
[0064] Curing system: The multi-layer fiber formed on the molding machine is pressurized and then enters the curing system for drying and curing. The curing system consists of a vacuum microwave system or a hot air furnace, a circulating fan, and a dehumidification fan. The vacuum microwave system uses a microwave with a power of 280kW to pre-oxidize and carbonize the surface treatment agent on the fiber surface (the fiber is heated by microwaves to gradually carbonize or volatilize the surface treatment agent, and the fiber is gradually cured into a new stable structure. The obtained lava fine fiber has excellent mechanical strength and temperature resistance). The hot air furnace uses an electric heating wire to heat the air and then blow it into the curing furnace to cure the fiber surface treatment agent. The fiber layer in the curing furnace is pressurized by the upper and lower chain plates and dried and cured by hot air penetration. According to the requirements of different types of surface agents, the microwave or hot air temperature is 220-245℃, and the curing time is 0.25h. The pure electric thermocouple hot air penetrates the fiber layer to recycle part of the heat energy. The dehumidification fan removes the hot and humid air in the curing furnace, and it is discharged after purification in the curing furnace filter chamber and spray system.
[0065] Slitting system: The dried and solidified fiber felt enters the crushing section after the cooling section and the cutting section. The cooling section is equipped with a negative pressure bellows under the horizontal conveying roller, and the negative pressure air penetrates the surface layer to take away the heat and cool it down. The cutting section is equipped with high-speed rotating longitudinal cutting saws and cross-cutting saws. When changing product varieties or when the back-end equipment fails, the products on the production line can be taken out from this part to ensure normal production in the front section, and then put into the back-end processing after recovery to ensure the continuity of production.
[0066] The slitting system includes a fiber high-speed rotary cutter and a gravity slag removal system. The fiber cutting length is controlled by adjusting the fiber cutter rotation speed parameters according to product specifications. The cut fibers enter the negative pressure pipeline and first enter the gravity slag removal to separate the coarser diameter slag balls, and then pass through the cyclone to further separate the smaller slag balls in the fiber. Finally, the exhaust gas is discharged through the bag dust collector to obtain lava fine fibers with an average diameter of 4.6μm.
[0067] Packaging system: Lava fine fibers are packaged and stored in an automatic packaging system according to product categories, specifications, uses, etc. The waste gas generated during the slitting and packaging process is purified by a bag filter and then discharged in a qualified manner.
[0068] Table 1 Performance comparison results of basalt fiber and lava fine fiber
[0069]
[0070]
[0071] The performance comparison results of the lava fine fiber prepared by the present invention and the basalt fiber in the prior art are shown in Table 1. As can be seen from Table 1, the lava fine fiber provided by the present invention has high tensile strength and elastic modulus and a wide operating temperature range.
[0072] Table 2 Cost accounting table of lava fine fiber production per ton
[0073] Production cost per ton consumption Unit price (Yuan) Subtotal (Yuan) Lava rock (tons) 0.85 200 170 Functional stone (tons) 0.2 700 140 Electricity cost (kW·h) 1600 0.75 1200 Surface treatment agent 1 800 800 Artificial 1 150 150 Package 1 300 300 Electrodes and refractory materials 1 90 90 Consumables 1 80 80 Depreciation 1 150 150 total - - 3080
[0074] Table 2 is the production cost accounting table of lava fine fiber per ton. It can be seen from Table 2 that lava fine fiber consumes 1,600 kWh of electricity per ton, while basalt fiber consumes 5,500 kWh of electricity per ton. The energy consumption of lava fine fiber per ton of finished fiber is about 30% of that of basalt fiber. The cost of lava fine fiber per ton is about 3,000 yuan, while the cost of basalt fiber per ton is about 10,000 yuan. The raw material cost of lava fine fiber per ton of finished fiber is about 35% of that of basalt fiber.
[0075] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing lava fine fibers, characterized in that: The following steps are involved: The lava ore and the functional ore are mixed and melted to obtain a melt; The melt is subjected to integrated fiber forming by spraying, spinning and blowing to obtain a fiber semi-finished product; The semi-finished fiber product and the surface treatment agent are mixed and then solidified to obtain lava fine fibers; The mass ratio of the lava ore to the functional ore is greater than 8:2; the functional ore includes iron ore, zircon, silica and bauxite; The integrated fiber forming by spraying, spinning and blowing includes simultaneously performing fiber forming by spraying and fiber forming by spinning.
2. The preparation method according to claim 1, characterized in that: Calculated by mass percentage, the chemical composition of the lava ore includes: 44-47% silicon oxide, 15-18% aluminum oxide, 17-20% calcium oxide, 7-10% magnesium oxide, 5-8% iron oxide and 1-2% titanium oxide.
3. The preparation method according to claim 1, characterized in that: Calculated by weight, the functional ore includes: 0.5 to 3 parts of iron ore, 2 to 3 parts of zircon, 4 to 6 parts of silica and 8 to 12 parts of bauxite.
4. The preparation method according to claim 1, characterized in that: The surface treatment agent includes a film-forming agent and a silane coupling agent; The film former includes one or more of epoxy resin, polyester resin, polyurethane resin and vinyl resin.
5. The preparation method according to claim 1 or 4, characterized in that: The mass ratio of the fiber semi-finished product to the surface treatment agent is 100:0.2-2.
6. The preparation method according to any one of claims 1 to 3, characterized in that: The melting temperature is 800-1500° C. and the melting time is 6-8 hours.
7. The preparation method according to claim 1, characterized in that: The wind speed of the blowing fiber forming is 80-120 m / s, and the blowing pressure is 25-35 kPa; the rotation speed of the spinning fiber forming is 5000-7500 rpm, and the line speed is 90-140 m / s.
8. The preparation method according to claim 1, characterized in that: The curing includes microwave curing; the curing temperature is 180-250° C. and the curing time is 0.2-0.3 h.
9. The lava fine fiber obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The lava fine fiber has an average diameter of 3 to 6 μm, a tensile strength of 2600 to 4200 MPa, and an elastic modulus of 85 to 110 GPa.
10. Use of the lava fine fibers according to claim 9 in reinforced composite materials, fire-resistant heat-insulating materials or filter materials.
Citation Information
Patent Citations
Method for preparing rock wool by utilizing cinder and phosphate tailings
CN102701583A
A method for producing basalt fibers by using a tank furnace method and the basalt fibers
CN110040971A
Preparation method of mineral fibers
CN112390544A
Alkali-resistant basalt continuous fibre and its production method
CN1272561A
Method for treating fibres, installation for treating fibres and thus obtained tape made of treated fibres
US20190232529A1
Cited By
Method for producing inorganic fibers by using high-temperature lava
CN121085549A
A method for producing inorganic fibers using high-temperature lava
CN121085549B
